2012
DOI: 10.1177/0269215512448382
|View full text |Cite
|
Sign up to set email alerts
|

The impact of occupational therapy in Parkinson’s disease: a randomized controlled feasibility study

Abstract: The positive perceived impact of occupational therapy warrants a large-scale trial. Adaptations in instructions and training are needed to use the Canadian Occupational Performance Measure as primary outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 35 publications
2
73
0
3
Order By: Relevance
“…The publication of feasibility studies before a planned RCT, especially related to process, resources, and management of the RCT, was unusual in the past and is now becoming more common in the broader medical literature. Publication of these types of studies is rare in occupational therapy (e.g., Sturkenboom et al, 2012). The typology developed by Thabane et al (2010) and slightly modified for occupational therapy intervention research provides guidance on how to approach pre-RCT studies systematically.…”
Section: Resultsmentioning
confidence: 99%
“…The publication of feasibility studies before a planned RCT, especially related to process, resources, and management of the RCT, was unusual in the past and is now becoming more common in the broader medical literature. Publication of these types of studies is rare in occupational therapy (e.g., Sturkenboom et al, 2012). The typology developed by Thabane et al (2010) and slightly modified for occupational therapy intervention research provides guidance on how to approach pre-RCT studies systematically.…”
Section: Resultsmentioning
confidence: 99%
“…Occupational therapy can help PD patients to better manage their problems in daily functioning and to facilitate meaningful activities and social participation. Evidence on occupational therapy long remained scarce, but one large randomized controlled trial has been reported on occupational therapy (Table ), which was informed by a pilot study . The study had two distinctive methodological innovations: first, the investigators enrolled and randomized couples rather than patients, because occupational therapy also targets the care partner; second, the intervention was delivered by occupational therapists who were PD specialists with extensive experience with PD, and part of the Dutch ParkinsonNet, specifically trained to deliver the intervention according to a best‐practice guideline.…”
Section: New Treatments and Discoveriesmentioning
confidence: 99%
“…As cognition plays an important role in instrumental activities of daily living, changes in cognition can have a significant negative influence on occupational performance and result in decreased quality of life and independence (Koerts et al, 2011;Pirogovsky et al, 2013). Thus, monitoring cognition is important for informing occupational therapy interventions with this population, which target optimising functional performance and engagement in activities of daily living and life roles (Sturkenboom et al, 2013).…”
Section: Introductionmentioning
confidence: 99%